Mechanical behavior of recycled polyethylene/piassava fiber composites - Elzubair, Amal; Miguez Suarez, João Carlos (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2012)
The use of natural fibers for reinforcement of thermoplastics (which are found in domestic waste) is desirable since it is based on abundant and renewable resources and can be ecologically correct. Leopoldinia piassaba Wallace (commonly known as piassava), a palm tree native of Amazon-Brazil, is cheap, easily found in Brazilian markets and the main component of home appliances and decorative goods. The subject of the present work is a study of mechanical properties of composites of recycled high density polyethylene (HDPE-r) reinforced with untreated, and treated (silane and NaOH) piassava fibers, in proportions varying from 0% to 20% and injection molded under fixed processing conditions. The influence of increasing amounts of piassava fibers and of surface treatment on the mechanical behavior of the composites was investigated by thermogravimetric analysis (TGA), mechanical testing (tensile and flexure) and scanning electron microscopy (SEM). The topography of the fractured surfaces of tested tensile specimens of unfilled and filled recycled HDPE was also observed by SEM and correlated with the mechanical behavior. As the fiber content increases, the composites show a gradual change in the mechanical properties and in the fracture mechanisms. Composites with 15% and 20% of piassava fibers were found to exhibit the best mechanical performance.